2020
DOI: 10.2217/cer-2019-0181
|View full text |Cite
|
Sign up to set email alerts
|

Assessing risk of bias judgments for blinding of outcome assessors in Cochrane reviews

Abstract: Aim: Adequate judging of risk of bias (RoB) for blinding of outcome assessors (detection bias) is important for supporting highest level of evidence. Materials & methods: Judgments and supporting comments for detection bias were retrieved from RoB tables reported in Cochrane reviews. We categorized comments, and then compared judgment and supporting comment with instructions from the Cochrane Handbook. Results: We analyzed 8656 judgments for detection bias from 7626 trials included in 575 reviews. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 15 publications
1
17
0
2
Order By: Relevance
“…On the contrary, for the domain regarding blinding of outcome assessors, we found that it would be beneficial to introduce sub-domains for objective versus subjective outcomes. This approach would decrease the number of undefined outcomes with a subsequent increase in the prevalence of adequate assessments [16]. We also found that length of comment impacts proper justification of an RoB judgment and its adequacy [7].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…On the contrary, for the domain regarding blinding of outcome assessors, we found that it would be beneficial to introduce sub-domains for objective versus subjective outcomes. This approach would decrease the number of undefined outcomes with a subsequent increase in the prevalence of adequate assessments [16]. We also found that length of comment impacts proper justification of an RoB judgment and its adequacy [7].…”
Section: Discussionmentioning
confidence: 73%
“…For the RoB domain for random sequence generation and allocation concealment accompanying comments were categorized to bring judgment as described in our previous studies [ 8 , 10 ]. For the blinding domains, we needed to determine which subject was blinded and whether the outcome(s) were susceptible to lack of blinding [ 7 , 16 ]. In the final stage, the prevalence of inadequate assessments was compared and reasons for inadequate RoB assessments between surgical and non-surgical trials stated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDSR was searched for all reviews of randomized controlled trials (RCTs) of interventions (or both RCTs and non-randomized studies, but we analyzed RoB assessments only for RCTs) published from July 2015 to June 2016. This was a large, one-year convenient sample based on our previous studies [8,11,12], four years after the introduction of the 2011 RoB tool when it is expected from the review authors to have adopted the new methodology (tool). An advanced search option was used to limit results to content type and publication date.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…More specifically, in the performance bias domain, the overall proportion of RoB judgments following the recommendations from Cochrane Handbook (adequate judgments) was 73.6%, and the main error in reported RoB judgments was the presumption of healthcare providers being adequately blinded [11]. In the detection bias domain, the frequency of adequate judgments was 77.9%, and the main error was the improper categorization of outcomes (subjective vs. objective) [12]. Furthermore, we noticed that Cochrane authors still frequently use the joint domain for blinding of key individuals by making modifications to the 2011 Cochrane RoB tool, even though the tool contains two distinct blinding domains.…”
mentioning
confidence: 99%